2020
DOI: 10.18502/avr.v29i4.4638
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hearing loss in infants hospitalized in the neonatal intensive care units

Abstract: Background and Aim: Studies have shown that several factors affect the hearing loss of infants hospitalized in the neonatal intensive care unit (NICU). These factors include hyperbilirubine­mia, low birth weight, asphyxia, and prematurity. This study aimed to investigate the prevalence of hearing loss and its risk factors in NICU infants. Methods: This is a cross-sectional study. Sam­ples were 159 infants admitted to the NICU in Fatemieh and Shahid Beheshti hospitals in Ham­adan, Iran, who were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…The highest percentage of cases with temporary hearing impairment (47.1%) was noticed among those who received aminoglycosides alone. This is similar to the study of (Gohari et al, 2020) in which ototoxicity was the most prevalent risk factor with a significant association between hearing loss and antibiotic therapy. Another study by (Abu Moussa & El Huchi, 2015) reported that there was no statistically significant deterioration in OAEs between group 2 (no antibiotics) and group 1 (received gentamycin only).…”
Section: Discussionsupporting
confidence: 87%
“…The highest percentage of cases with temporary hearing impairment (47.1%) was noticed among those who received aminoglycosides alone. This is similar to the study of (Gohari et al, 2020) in which ototoxicity was the most prevalent risk factor with a significant association between hearing loss and antibiotic therapy. Another study by (Abu Moussa & El Huchi, 2015) reported that there was no statistically significant deterioration in OAEs between group 2 (no antibiotics) and group 1 (received gentamycin only).…”
Section: Discussionsupporting
confidence: 87%
“…One of the risk factors studied in the present study was ventilation. A study by Gohari showed no significant relationship between a ventilation risk factor and hearing loss [ 23 ]. This finding is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been less attention in previous studies. In the study of Gohari no significant correlation was found between kinship marriages of parents and hearing loss [ 23 ]. In the Khuzestan province, due to the cultural context, the kinship marriage of parents is one of the risk factors for hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an association was found between HL and the following factors: at least one Joint Committee on Infant Hearing (JCIH) risk factor, NICU admission for five or more days, LBW, postnatal hypoxia, and forceps delivery. It has also been demonstrated by Choi et al [ 15 ], Gohari et al [ 16 ], Hajare and Mudhol [ 10 ], and Hardani et al [ 17 ] that a multitude of factors influence the HL of infants seeking treatment in the NICU.…”
Section: Reviewmentioning
confidence: 92%
“…The findings of the review revealed a wide variety of maternal and neonatal factors that have an impact on HL in children. Studies that were included in this review were conducted in a number of different countries, which include India [ 10 , 26 ], Egypt [ 11 ], Korea [ 14 , 15 ], Iran [ 16 , 17 ], Gaza [ 13 ], Jordan [ 23 ], Nigeria [ 20 ], Poland [ 21 ], Sweden [ 18 ], Thailand [ 22 ], Italy [ 12 ], Brazil [ 19 ], and Turkey [ 24 , 25 ]. Overall, the majority of these studies have appraised the role of a variety of maternal and neonatal factors related to HL.…”
Section: Reviewmentioning
confidence: 99%